QoSS Hierarchical NoC-Based Architecture for MPSoC Dynamic Protection. (19th July 2012) - Sepulveda, Johanna; Pires, Ricardo; Gogniat, Guy; Chau, Wang Jiang; Strum, Marius
Abstract : As electronic systems are pervading our lives, MPSoC (multiprocessor system-on-chip) security is becoming an important requirement. MPSoCs are able to support multiple applications on the same chip. The challenge is to provide MPSoC security that makes possible a trustworthy system that meets the performance and security requirements of all the applications. The network-on-chip (NoC) can be used to efficiently incorporate security. Our work proposes the implementation of QoSS (quality of security service) to overcome present MPSoC vulnerabilities. QoSS is a novel concept for data protection that introduces security as a dimension of QoS. QoSS takes advantage of the NoC wide system visibility and critical role in enabling system operation, exploiting the NoC components to detect and prevent a wide range of attacks. In this paper, we present the implementation of a layered dynamic security NoC architecture that integrates agile and dynamic security firewalls in order to detect attacks based on different security rules. We evaluate the effectiveness of our approach over several MPSoCs scenarios and estimate their impact on the overall performance. We show that our architecture can perform a fast detection of a wide range of attacks and a fast configuration of different security policies for several MPSoC applications.